KEPEMIMPINAN PEREMPUAN (FEMALE LEADERSHIP): TAFSIR AYAT TENTANG PERAN PUBLIK WANITA - Siti Maryam Nst; Roma Rizkina Fatimah Pulungan; Ali Akbar (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study examines female leadership in the public sphere based on the interpretation of Qur'anic verses. Using a thematic exegesis approach to verses related to women's roles in society, this research explores the proper understanding of women's positions and roles in public domains within the Islamic perspective. The findings reveal that the Qur'an grants fair space for women to assume leadership roles and actively participate in social and political fields, while maintaining Islamic values. This study provides a theoretical foundation to reinforce women's roles as responsible and integrity-driven public leaders.